On the Mechanism of Proton Transport by the Neuronal Excitatory Amino Acid Carrier 1 - Watzke, Natalie (The Rockefeller University Press, 2000)
Uptake of glutamate from the synaptic cleft is mediated by high affinity transporters and is driven by Na(+), K(+), and H(+) concentration gradients across the membrane. Here, we characterize the molecular mechanism of the intracellular pH change associated with glutamate transport by combining current recordings from excitatory amino acid carrier 1 (EAAC1)–expressing HEK293 cells with a rapid kinetic technique with a 100-μs time resolution. Under conditions of steady state transport, the affinity of EAAC1 for glutamate in both the forward and reverse modes is strongly dependent on the pH on the cis-side of the membrane, whereas the currents at saturating glutamate concentrations are hardly affected by the pH. Consistent with this, the kinetics of the pre–steady state currents, measured after saturating glutamate concentration jumps, are not a function of the pH. In addition, we determined the deuterium isotope effect on EAAC1 kinetics, which is in agreement with proton cotransport but not OH(−) countertransport. The results can be quantitatively explained with an ordered binding model that includes a rapid proton binding step to the empty transporter followed by glutamate binding and translocation of the proton-glutamate-transporter complex. The apparent pK of the extracellular proton binding site is ∼8. This value is shifted to ∼6.5 when the substrate binding site is exposed to the cytoplasm.